THE EFFECTIVENESS OF TEACHERS’ INDIRECT FEEDBACK FOR STUDENTS’ WRITING PERFORMANCE ON DESCRIPTIVE TEXT - Aisyah Kamilia; Bitadwi Rahmani; Siswana Siswana (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2020)
This quasi-experimental study aimed to discover the empirical evidence on the effectiveness of employing teachers' indirect feedback on students' writing skills of the descriptive text in one senior high school in Indonesia. The participants of the research are 52 students in total comprising 26 students from the science program class assigned as the experimental group, and 26 students from social program class as a control group. This research implemented teachers' indirect feedback in the experimental group for 6 meetings with the descriptive text topic based on the 2013 curriculum. On data collection, the descriptive writing test was employed, then, the data was analyzed by using SPSS version 25 software program. Based on the analysis of the data, it is yielded that there is a significant increase in the mean of post-test scores of the science class which is from 62.84 to 79.97. In addition, the post-test means score in the social class growth as well from 58.96 to 63.00. It is assumed that the implementation of teachers' indirect feedback is effective to improve students’ skills in writing descriptive text.